Laser- and Ion-Induced Defect Engineering in WS2 Monolayers - Asaithambi,A; Kozubek,R; Prinz,GM; Reale,F; Pollmann,E; Ney,M; Mattevi,C; Schleberger,M; Lorke,A (Physica Status Solidi Rapid Research Letters, 2021)
Tungsten disulfide is one of the prominent transition metal dichalcogenide materials, which shows a transition from an indirect to a direct bandgap as the layer thickness is reduced down to a monolayer. To use (Formula presented.) monolayers in devices, detailed knowledge about the luminescence properties regarding not only the excitonic but also the defect-induced contributions is needed. Herein, (Formula presented.) monolayers are irradiated with (Formula presented.) ions with different fluences to create different defect densities. Apart from the excitonic contributions, two additional emission bands are observed at low temperatures. These bands can be reduced or even suppressed, if the flakes are exposed to laser light with powers up to 1.5 mW. Increasing the temperature up to room temperature leads to recovery of this emission, so that the luminescence properties can be modified using laser excitation and temperature. The defect bands emerging after ion irradiation are attributed to vacancy defects together with physisorbed adsorbates at different defect sites.